Molecular diagnosis for camel raw milk microbiota: Molecular diagnosis for microbiota - Ahmed, Mohamed Morsi M.; Alsulaimany , Faten A.S.; Alattas, Sana Ghazi; Al-Garni, Saleh M. (Cellular and Molecular Biology, 2024)
The existence of diverse microbes in unprocessed camel milk poses a significant threat to the well-being of a large population, especially infants and toddlers. The objective of this study was to ascertain the existence of microorganisms in unprocessed raw camel milk by employing a molecular-based technique in combination with a histological examination of bacteria. The identification of microbial species was achieved by employing PCR amplification and sequencing of 16s rRNA gene fragments. Various micorganisms found includes the probiotic Lactobacillus species, Staphylococcus succinic, Macrococcus casealyticus, Bacillus cohnii, and Salinicoccus kunmingensis. To prevent microbial contamination in raw milk, it is necessary to adequately heat or pasteurise the milk and to wash and sterilise the udder before milking the camel. This is because raw milk contains microbes that cause multiple diseases. Moreover, in the current era of the COVID-19 pandemics, ensuring proper sanitary conditions in milk and its derivatives might potentially mitigate the transmission of various diseases among consumers shortly. Keywords: camel, microbiota, 16s rRNA gene, PCR.